Impacts of different roof designs and air-conditioning operations on energy consumption and costs in air-conditioned mosques in the Klang Valley , Malaysia - Mohamed, Nur Amalina Syairah (2022)
Energy efficiency in mosques, particularly in Malaysia, receives little attention even though this building typology has a significant total floor area comparable to commercial buildings. Although roofs are the major contributors to buildings' energy consumption and mosques generally have a unique occupancy and energy use pattern, there are scant records on the effect of roof designs on energy consumption for air-conditioned mosques in Malaysia. Furthermore, using air-conditioning (AC) in conjunction with high-volume low-speed (HVLS) fan has become a trend in retrofitted mosque buildings in Malaysia to improve thermal comfort conditions. However, the energy impact of operating AC and HVLS fan simultaneously is unknown. Therefore, this study aims to investigate the impacts of different roof designs and adjustments of AC temperature setpoints and operational profiles on the energy consumption and costs of air-conditioned mosques in the Klang Valley with the following objective: 1) To identify and classify the specific roof forms designed for air-conditioned mosques built in the Klang Valley between 1998 and 2018., 2) To analyse and compare the BEIs and electricity costs of air-conditioned mosques with different roof forms and between those with and without HVLS fan, and 3) To assess air-conditioned mosques' energy and cost savings potential through different air-conditioning temperature setpoints and operational profiles adjustments. A total of 467 mosques were identified in the Klang Valley, and 54 were found to comply with the selection criteria. Based on these 54 mosques, the study identified three roof classifications, namely "dome on flat roof", "dome on pitch roof", and "no dome", with "dome on pitch roof" being the most popular roof type. Five mosques were selected to represent these three roof classifications, and their BEIs were calculated and compared using 2-5years' electricity bill data. The BEI of mosques with and without HVLS fans were also compared. Then, two mosques with the highest BEI were further investigated through computer simulations to determine the optimum AC operational profile and temperature setpoints to reduce the mosques’ energy consumption. The mosque with "dome on flat roof" had the highest BEI, i.e. 204 kWh/m2/yr and 230 kWh/m2/yr based on 5-year and 2-year electricity bills, respectively. From the simulations, both studied mosques could produce around 1-4.9% energy reduction when the AC temperature setpoint was increased by 1˚C and could result in the highest cost-saving of about 4.9% when the temperature was set at 27˚C. A 30-minute AC operation during each daily prayer, except Subuh, could save between 14.8-16.7% annual energy consumption and about 15.2-16.6% annual energy cost. The study concludes that the selection of 24-27˚C temperature setpoints with a 30-minute AC operational profile during prayers time, considering Friday prayers and Ramadan activities, produced 18.4-20.6% savings in energy cost. This study provides the BEI results for energy benchmarking of a typical air-conditioned mosque in the Klang Valley. It calls for the AC temperature setpoints configuration standards and operational profiles of existing mosques to be reevaluated to reduce their energy consumption. Ultimately, it will contribute to developing future energy standards for mosque designs and operations in Malaysia.